The Shadow Banking Dilemma: A Critical Appraisal Of Its Effects In India (Journal of Namibian Studies : History Politics Culture, 2023)
The shadow banking system is a web of specialised financial institutions that channel funding from savers to investors through a range of securitisation and secured funding techniques. Although shadow banks the institutions that constitute the shadow banking system - conduct credit and maturity transformation similar to that of traditional banks, they do so without the direct and explicit public sources of liquidity. This Paper provides the empirical, theoretical and conceptual foundation for the study. The authors argue that shadow banking activities increase the probability of a crash in the economy. In spite of its critical function, the NBFC sector in India is plagued by the following issues: Expense of borrowing money, the sluggish expansion of industry, there is intense rivalry from non-bank financial institutions (NBFCs) and the banking industry, ineffective investments and inadequate recovery methods. With this study, we hope to learn more about the pervasive challenges faced by NBFCs and assess the state of their finances as a whole.